The complexity of premenstrual dysphoric disorder - risk factors in the population of Polish women - Nowosielski Krzysztof; Drosdzol Agnieszka; Skrzypulec-Plinta Violetta; Plinta Ryszard (BMC, 2010)
Abstract Background Premenstrual dysphoric disorder has multiple determinants in the biological, psychological and socio-cultural domains. The aim of the study was to evaluate the risk factors for premenstrual dysphoric disorder in Polish women, considering their reproductive history, socio-economic factors, as well as lifestyle and health-related factors. Methods 2,500 females, aged 18 to 45, from the Upper Silesian region of Poland were eligible for the prospective population study. The final study sample was 1,540 individuals. The research was based on a questionnaire containing socio-economic status, general health, lifestyle, medical and reproductive history, premenstrual symptoms based on the American Psychiatric Association's criteria for diagnosing premenstrual dysphoric disorder, and patient prospective daily ratings of symptoms. The Statistica 8.0 computer software was used for statistical analysis. The value of p < 0.05 was adopted as the level of statistical significance. Results The mean age of the studied population was 31.9 +/- 7.3 years. The majority of the studied women were married (57.9%), lived in large cities (42.0%) and had tertiary education (43.2%). The results of the study indicated that the prevalence of premenstrual dysphoric disorder was 2.1%. The final statistical analysis revealed that only tertiary education decreased the risk of premenstrual dysphoric disorder (OR = 0.08; p < 0.05). Conclusions Our research showed that women with tertiary education are less vulnerable to premenstrual dysphoric disorder than women with a lower level of education. Reproductive and lifestyle factors seem to be play a lesser role.